Construct validity of the pictorial scale of Perceived Movement Skill Competence. (January 2016) - Barnett, Lisa M.; Vazou, Spyridoula; Abbott, Gavin; Bowe, Steven J.; Robinson, Leah E.; Ridgers, Nicola D.; Salmon, Jo
Abstract: Objectives: The Pictorial Scale of Perceived Movement Skill Competence (PMSC) assesses young children's perceptions of movement skill competence: 12 perceived Fundamental Movement skills (FMS; based on the Test of Gross Motor Development 2nd edition TGMD-2) and six Active Play activities (e.g. cycling). The main study purpose was to assess whether children's movement perception scores fit within the imposed constructs of Active Play and FMS by testing the latent structure and construct validity of the PMSC. Design: Construct validation study. Methods: Participants were part of the Melbourne Infant Feeding, Activity and Nutrition Trial (InFANT). The latent structure of the PMSC responses was tested through confirmatory factor analysis (CFA) and Bayesian Structural Equation Modeling (BSEM). Internal consistency was conducted using polychoric correlation-based alphas. Results: The 303 children (boys 53.1%, n = 161) were aged 4–5 years ( M  = 4.7, SD = 0.46). The final model had an 18 item 3-factor solution with good fit indices (using CFA and BSEM). Factors were: Active Play (Bike, Board Paddle, Climb, Skate/Blade, Scooter, and Swim), Object Control – Hand Skills (Bounce, Catch, Hit, Throw), and FMS skills with a leg action (Gallop, Hop, Jump, Leap, Run, Step Slide, Kick, Roll). Alpha reliability values were: Active Play (0.78), Object Control-Hand Skills (0.76) and FMS-Dynamic Leg (0.84). Conclusion: Young children can distinguish between movement perceptions. The factors reflect the hypothesized structure in terms of FMS being distinguished from Active Play. Further research should investigate how and if these constructs change in children over time. Highlights: There is currently no comprehensive assessment of young children's movement competence perceptions. This study has shown young children can distinguish between their perceived ability in FMS and Active Play. Children identified object control skills performed with the hands as a distinct factor.